PREDIKSI KEKUATAN STRUKTUR TRUSS 2D KOMPOSIT BAJA RINGAN-KAYU LAMINASI - , HENDY LINGGO WIBOWO; , Dr.-Ing. Ir. Andreas Triwiyono ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cold formed steel roof truss structure as a building material is now widely used. However, cold formed steel truss structure has a weakness in buckling caused by ratio between width to thickness ratio of the flange or web. Therefore, efforts should be developed to increase the buckling strength of cold formed steel for example by combining it with timber into a composite structure with shear connectors. The experiments include two series of cold formed steel truss and composite truss experimentally (fullscale) with Howe roof type, span 600 cm, 173 cm high with a slope angle of 30o. The composite trusses Z profile 75x30 mm and C profile 65x25 mm 0.80 mm thick with mahogany timber filler which is an alternative material on axial stress of trusses and compare to cold formed trusses. The truss structure test used 3-point static loading gussets and then measured deflection and the maximum loads. The cold formed steel trusses fabricated and installed by distributor used two cold formed steel trusses with bracing, the composite used only single truss. Predictions based on the theoryl, load capacity of the composite truss will increase by 195 %. From the test results indicate that the composite truss is more stiff and ductile due to the influence of bracing, maximum load of CFS truss is 6.75 KN and deflection 11,05 mm (used single trusses) have not reached that permits deflection of L / 240 = 25 mm with failure on the restraints(pinned support) and compression axial force. The composite truss maximum load 11.646 KN, maximum deflection 37.1 mm and 25 mm deflection permit load is reached at 9.49 KN with buckling failure of the compression members. The load capacity of cold formed truss after composite with laminated timber increase 173 %. Keywords: cold formed steel, mahogany laminated timber, buckling failure, composite, truss structure